The effect of apparent distance on visual spatial attention in simulated driving - Jiali, Song (My University, 2021)
Much about visual spatial attention has been learned from studying how observers respond to two-dimensional stimuli. Less is known about how attention varies along the depth axis. Most of the work on the effect of depth on spatial attention manipulated binocular disparity defined depth, and it is less clear how monocular depth cues affect spatial attention. This thesis investigates the effect of target distance on peripheral detection in a virtual three-dimensional environment that simulated distance using pictorial and motion cues. Participants followed a lead car at a constant distance actively or passively, while travelling along a straight trajectory. The horizontal distribution of attention was measured using a peripheral target detection task. Both car-following and peripheral detection were tested alone under focussed attention, and simultaneously under divided attention. Chapter 2 evaluated the effect of target distance and eccentricity on peripheral detection. Experiment 1 found an overall near advantage that increased at larger eccentricities. Experiment 2 examined the effect of anticipation on target detection and found that equating anticipation across distances drastically reduced the effect of distance in reaction time, but did not affect accuracy. Experiments 3 and 4 examined the relative contributions of pictorial cues on the effect of target distance and found that the background texture that surrounded the targets could explain the main effect of distance but could not fully account for the interaction between distance and eccentricity. Chapter 3 extended the findings of Chapter 2 and found that the effect of distance on peripheral detection in our conditions was non-monotonic and did not depend on fixation distance. Across chapters, dividing attention between the central car-following and peripheral target detection tasks consistently resulted in costs for car-following, but not for peripheral detection. This work has implications for understanding spatial attention and design of advanced driver assistance systems.
Apparent Distance and Attention in Simulated Driving
Keywords: Perception; Attention; Depth; Distance; Useful field of view; Peripheral vision; Driving